PRESENTATION OF TYPHOID FEVER PATIENTS IN HAZARA DIVISION AND RESPONSE TO DIFFERENT TREATMENT REGIMENS - Nazar, Hassan Shahzad; Rabbani, Aftab; Riaz, Adeel; Anwar, Jasim (Journal of Ayub Medical College Abbottabad, 2005)
Background: Response to treatment can vary in patients with typhoid fever. This study was carried out on a group of typhoid patients who were treated in Medical B ward of Ayub Teaching Hospital. Resistance to antibiotic is commonly acquired by Salmonella typhi and is widely reported. Objective of study was to identify such resistance in patients coming from parts of Hazara Division. Methods: All patients who presented with typhoid fever and admitted to Medical B Unit from 1st July to 30th September 2002 were included in study. Out of 76 patients 46 (60%) were male. Epidemiological date, presenting symptoms, finding on physical examination, laboratory investigation and radiological examination were recorded. Then one of six commonly used treatment regimens were started. Response to treatment was studied. Results: Common presenting symptoms and signs were recorded. Headache and fever were seen in 100% of patients. Cough and hypotension were among presenting features in 65% of patients. Leucocyte count of Less than 4x103/dl was seen in 11% of samples. Liver functions and Renal function were found alterd in 30% of patients. Study of response pattern to different regimens suggested relatively poor response to flouroquinolones. Fever of those patients who were treated with chloamphenicol and cefexime ,settled early as compared to patients on other regimens. Conclusions. In addition to well known presenting features of typhoid like headache, fever, cough, hypotension and leucopenia abnormalities of renal and liver functions were commonly seen. Response to quinolone was poor suggesting emergence of resistance of salmonella typhi in this area. Key Words: Tyhpoid, Multiresistance in salmonella, Hazara, Quinolones, Chloroamphenicol.